2019
DOI: 10.1002/app.48767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of network mesh size and swelling to the drug delivery from pH responsive hydrogels

Abstract: pH responsive hydrogels are ideal platforms for numerous therapeutic delivery applications, including oral delivery, as they are capable of overcoming the many barriers that must be considered when creating an effective drug delivery system. Understanding of the innate hydrogel network structure and its swelling behavior at environmentally relevant conditions is vital for designing hydrogel network capable of effective controlled drug release. Herein, we explored how to expand traditional techniques of swellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Schematic representations for swollen polymer networks, also known as hydrogels, frequently oversimplify the structure. The most commonly used and symbolic schematic for a swollen polymer network has four polymer chains in an overlapping hash pattern, [ 1–4 ] implying that the network junctions are tetrafunctional and all chains are restricted to a 2D plane. In those representations, the network appears to form a square portal that a solute could pass through if its diameter was less than the length of one network chain between two junctions ( Figure A).…”
Section: Introductionmentioning
confidence: 99%
“…Schematic representations for swollen polymer networks, also known as hydrogels, frequently oversimplify the structure. The most commonly used and symbolic schematic for a swollen polymer network has four polymer chains in an overlapping hash pattern, [ 1–4 ] implying that the network junctions are tetrafunctional and all chains are restricted to a 2D plane. In those representations, the network appears to form a square portal that a solute could pass through if its diameter was less than the length of one network chain between two junctions ( Figure A).…”
Section: Introductionmentioning
confidence: 99%
“…As with solutes, analysis of how hydrogel properties affect solute diffusivity in hydrogels has focused on the relative sizes of molecular components. ,,,, Mesh size, which describes the average distance between two network junctions connected by a polymer chain, has been frequently associated with solute diffusivities in hydrogels via convenient, often simplified, correlations or scaling concepts. We recently suggested that the term “mesh radius,” which describes the expected radius of a hydrodynamically spherical solute that would pass through a hydrogel network portal, would be a more accurate predictor of solute diffusivity than mesh size .…”
Section: Introductionmentioning
confidence: 99%
“…Maximizing the permeability for water with retained mechanical durability is usually the goal in development of fast disintegrating tablets or extended-release coated tablets [12][13][14]. More sophisticated control of the drug release is usually expected for microspheres, implants or hydrogels, where swelling additionally contributes to the diffusion mechanism [15][16][17]. Although the approach of matrix modification with solid or liquid hydrophilic excipients to increase water transport or drug release was reported by other authors [18,19], the pore formation in PDMS materials suitable for transdermal drug delivery has been an unexplored topic.…”
Section: Introductionmentioning
confidence: 99%